Carbon onions coated Ni/NiO nanoparticles as catalysts for alkaline hydrogen evolution reaction. (20th October 2022) - Yan, Yuqi; Ma, Qinghai; Cui, Fang; Zhang, Jiajia; Cui, Tieyu
Highlights: Carbon onions coated Ni/NiO are synthesized base on a facile self-assembly method. Regulating the ratio of Ni/NiO has been proved to be effective for optimizing the kinetic process in alkaline HER and therefore improving HER activity. Ni/NiO/C-500 with a Ni/NiO ratio of 1.31 display an overpotential of 127 mV at 10 mA cm −2 for HER in 1 M KOH. The synergetic effect of Ni, NiO and c promote the HER activity of Ni/NiO/C composites. Abstract: High-performance carbon onions coated Ni/NiO nanoparticles (CNN NPs) acting as electrocatalysts in alkaline hydrogen evolution reaction (HER) is synthesized base on a self-assembly process combined with a calcination process. By systematically regulating the surface composition, we find that controlling the kinetic steps in HER by regulating the ratio of Ni/NiO can significantly promote alkaline HER activity, and CNN-500 with a Ni/NiO ratio of 1.31 display an overpotential of 127 mV (vs. RHE) at a current density of 10 mA cm −2 for HER in 1 M KOH electrolyte. The ratio of Ni and NiO active catalytic components are adjustable via controlling the calcination process, which play an important role in alkaline HER performance. Due to the synergistic effect between Ni, NiO and C, the CNN-500 shows superior intrinsic catalytic activity than that of currently reported HER electrocatalysts. This work provides a facile and useful strategy to get high-performance alkaline HER electrocatalysts for hydrogen energy source. Graphical abstract: Image, graphical abstract